Desenvolvimento de um programa educacional de formação continuada: o torna-se educador a partir de reflexões e (trans) formações em busca de melhoria do ensino e da aprendizagem. - Danaga, Nilce Helena Poiatti (2004)
The teaching democraticalization by Federal Constitution of 1988 and the National Education Basis and Guidelined Law 9394/96, provided opportunity of teaching for all and intensified the need of educational system changes for better theaching quality. Aiming to reduce the school failure, the public politics for education have been prodigal in the variety of alfabetization, assessment, recovering of the not-understood contents end even school physical space use programs. The teacher s capacitation became a Education s Ministry preocupation, so was stablished in 2001 the PROFA Programa de Formação de Professores Alfabetizadores (Program of Formation Alphabet Teachers) with assistence of the municipal teaching system. Bringing a course of didactics contents and procedures improvement with a theoric base settled in a vast bibliography with psychologist and socialist character, this program had as the initial purpose to guide the teachers and to contribute for the development of their abilities in the alphabet process. However, would the PROFA s purposes change the teacher s practice, and improved the children apprenticeship? The answer for this was seeked by developing a case study with a qualitative investigation aiming to know entirely the PROFA, to mark each proposal stage, to follow the application of activities in fundamental school classrooms as well the children development and aprenticeship. Associating a bibliography study, a documental analysis, interviews and participant comment, was following during the year of 2002 the classroom s activities of teachers from first stage of Coronel Tobias Fundamental Education Municipal School in Descalvado SP. The methodological directions application of the PROFA provided a children progress on reading, hand-writing and oral interpretation, and text production, but not enaigh for all of them take the same profit during the year. Also the subsidies given by the PROFA were accepted and applied by the teachers at the daily activities school. Was concluded that it is important the need of the evaluation of paradigms of Formation that provides the preparation of teachers more reflexive and committed with education to incorporate effectiveness the contents didactic-methodologicals given by the Program like this in the daily pratice professional of the educators. As well efficient public politics, the pedagogic promises of all professional in this area is very important to get education improvement, including the commitment between teachers, co-ordenators, supervisors and director of the school. Is not possible to change it if the educators save efforts to get it done, they must play their role in this process.